2008
DOI: 10.1149/1.2910230
|View full text |Cite
|
Sign up to set email alerts
|

An XAFS Study of Nickel Chloride in the Ionic Liquid 1-Ethyl-3-Methyl Imidazolium Chloride/ Aluminum Chloride

Abstract: Nickel chloride was studied with cyclic voltammetry and X-ray absorption spectroscopy in acidic and basic aluminum chloride/1-ethyl-3-methyl imidazolium chloride (EMIC) ionic liquids. Acidic melts display metal stripping peaks which are not observed in the basic melt. EXAFS analysis shows that the nickel is tetrahedrally coordinated with chloride ions in the basic solution. In the acidic solution the nickel is coordinated by six chloride ions that are also associated with aluminum ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Earlier research has shown that nickel metal and nickel alloys can be deposited from nickel chloride dissolved in the IL EMIC/AlCl 3 12 but this depended on Lewis acidity of the IL which in turn affects the structure of the Ni ions that form in the solution. 12,13 In order to understand the electrodeposition of the transition metals and their alloys, the structures of several transition metal chlorides have been studied in situ in ionic liquids using EXAFS. [12][13][14][15][16][17][18] However, the oxides of these metals have not received as much attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has shown that nickel metal and nickel alloys can be deposited from nickel chloride dissolved in the IL EMIC/AlCl 3 12 but this depended on Lewis acidity of the IL which in turn affects the structure of the Ni ions that form in the solution. 12,13 In order to understand the electrodeposition of the transition metals and their alloys, the structures of several transition metal chlorides have been studied in situ in ionic liquids using EXAFS. [12][13][14][15][16][17][18] However, the oxides of these metals have not received as much attention.…”
mentioning
confidence: 99%
“…12,13 In order to understand the electrodeposition of the transition metals and their alloys, the structures of several transition metal chlorides have been studied in situ in ionic liquids using EXAFS. [12][13][14][15][16][17][18] However, the oxides of these metals have not received as much attention. When working with the water and air sensitive ILs, there is always a concern about oxygen and moisture contamination and its effect on the properties of the IL.…”
mentioning
confidence: 99%
“…12,13 Gilbert et al investigated the electrochemical properties of nickel in molten salts consisting of AlCl 3 and KCl at 175-210 • C. 14 On the other hand, electrochemical properties for molten salts containing AlCl 3 and organic salts have also been widely studied. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Such chloroaluminate salts vary their melting points, decreasing to lower temperature as they approach, by changing the ratio of AlCl 3 and organic salts, although their ion conductivity has been reported to be well maintained. Accordingly, many studies have been done on electrochemical properties for chloroaluminate salts with organic salts at around 100 • C or ambient temperature in view of application for batteries as well as electro-deposition of metals and sensors.…”
mentioning
confidence: 99%
“…O'Grady et al also intensively investigated the electrochemical properties of NiCl 2 with cyclic voltammetry and other metals that were first dissolved in AlCl 3 -EMIC and then deposited on to the Pt plate at room temperature. [23][24][25][26] They analyzed the electrolyte after oxidizing nickel but did not identify the product of NiCl 2 on the Pt electrode. 23 Kohl et al also studied some metals behavior in the NaCl-buffered AlCl 3 -EMIC salt.…”
mentioning
confidence: 99%
See 1 more Smart Citation